One or Two Roots? Yi Zhi and the Dilemma of Practical Reason - Xie, Xiaodong (Religions, 2022)
Mohism has two versions of ethics, attributed to Mozi and Yi Zhi 夷之, respectively. Mozi introduced an ethics usually described as utilitarian, emphasizing universal love as the basis of impartiality. However, the problem with this emphasis is that it leads to neglecting the development of rational self-interest. Accordingly, Yi Zhi’s remarks are a clarification or modification of Mozi’s thoughts. First, Yi Zhi alluded to the concept of undifferentiated love to explain universal love as the basis of impartiality. Second, as he understood the concept of undifferentiated love in relation to the idea that “bestowing love begins with one’s parents”, Yi Zhi incorporated rational self-interest. Moreover, Mencius criticized Yi Zhi and disparaged his remarks as two roots (二本 er ben), contrasting it to Confucian ethics, which he said was one root. This division between one root (一本 yi ben) and two roots has garnered significant attention. On the one hand, Zhu Xi believed that the essence of two roots is undifferentiated love, wherein he concluded that it is applicable to both Mozi and Yi Zhi. On the other hand, most later scholars interpreted two roots from an ethical perspective, arguing that Yi Zhi faced the dilemma of two conflicting moral theories. Considering the basic principles of moral philosophy, the ethics of Mozi and Confucius are one root, and only that of Yi Zhi is two roots. This article shows that Yi Zhi and Henry Sidgwick, the founder of classical utilitarianism, face the same dilemma of practical reason: the conflict between utilitarianism and the self-interest of egoism.